Novel efficiency of turmeric extract as a green inhibitor of low carbon steel corrosion in 3.5% NaCl solution - Hajir Amer Jaddoa; Basheer A. Abdulhussein; Jamal M. Ali (Case Studies in Chemical and Environmental Engineering)
Carbon steel's atmospheric corrosion susceptibility is well-studied. Marine chlorides were poorly studied until recently. Because of their importance to civilization, coastal areas are prone to corrosion. As developing nations industrialize, they move production facilities to coastal areas, where half the world's population lives. Little was known about rust formation in Cl-rich environments before the millennium. Recently, we understand marine atmospheric corrosion better. An aqueous turmeric powder extract is used as a corrosion inhibitor to control low carbon steel corrosion in 3.5 % NaCl. Weight loss and polarization studies were used. A FTIR spectrum was used to analyze the protective film, FESEM examined surface morphology and AFM. Metal hardness before and after immersion is known. A weight loss study found that 1200 ppm turmeric extract inhibits corrosion at 97.52 %. Use these findings in petroleum equipment.